The efficacy of LASIK and secondary piggyback IOL implantation for the enhancement after cataract surgery - E.P. Gurmizov; K.B. Pershin; N.F. Pashinova; A.Yu. Tsygankov (РМЖ "Клиническая офтальмология")
The efficacy of LASIK and secondary piggyback IOL implantation for the enhancement after cataract surgery E.P. Gurmizov1, K.B. Pershin2, N.F. Pashinova2, A.Yu. Tsygankov2 1LLC “Diagnostic Center “Vision”, St. Petersburg, Russian Federation 2LLC “SovMedTech”, Moscow, Russian Federation Aim: to compare the efficacy of laser-assisted in situ keratomileusis (LASIK) and secondary piggyback intraocular lens (IOL) implantation for residual refractive errors after cataract surgery. Patients and Methods: prospective open-label study included 74 patients (98 eyes) who underwent cataract surgery (53 eyes) or refractive lens exchange (45 eyes) with the implantation of various IOL models. Inclusion criterion was residual refractive error persisted for 6 months or more after IOL implantation that required additional surgery. Of 74 patients, 52.7% (n=37) were men and 47.3% (n=35) were women. Mean age was 51.7±11.2 years (19–86 years). Group I included 50 patients who underwent standard LASIK (72 eyes). Group II included 24 patients (26 eyes) who underwent secondary piggyback IOL implantation (Rayner Sulcoflex, 19 eyes, or Add-onTorica-sPB A4FW, 7 eyes). Results: in group I, no significant changes in spherical equivalent were revealed postoperatively (0.38±1.37 and 0.33±0.55, respectively). Cylindrical equivalent reduced from -0.93±1.35 to -0.12±0.73 (p<0.05). Distance uncorrected visual acuity (UCVA) significantly improved after a maximum follow-up from 0.37±0.16 to 0.76±0.19 (p<0.05) while distance best-corrected visual acuity (BCVA) remained unchanged. In group II, distance UCVA significantly improved from 0.26±0.21 to 0.84±0.16 (p<0.05) while distance BCVA improved from 0.85±0.16 to 0.89±0.15 (p>0.05). Spherical and cylindrical equivalents reduced from -0.07±3.3 to 0.02±0.4 and from -1.17±2.4 to -0.55±0.91, respectively (p>0.05). No significant changes in keratometry readings were revealed (p>0.05). Safety index was 1.03 in group I and 1.06 in group II (p>0.05). Efficacy index was 0.92 in group I and 0.99 in group II (p>0.05). Conclusion: our findings demonstrate that both LASIK and secondary piggyback IOL implantation are effective for residual refractive errors after cataract surgery. Significant improvement of distance UCVA was revealed in both groups. LASIK results in significant decrease of cylindrical equivalent. Efficacy and safety indices were similar in the groups. Secondary piggyback IOL implantation is recommended for residual high myopia and hyperopia while LASIK is recommended for residual low to moderate myopia and low hyperopia. Therefore, both enhancement techniques may be applied in ophthalmological practice. Keywords: pseudophakia, LASIK, secondary piggyback IOLs, femtoLASIK, enhancement, residual refractive error. For citation: Gurmizov E.P., Pershin K.B., Pashinova N.F., Tsygankov A.Yu. The efficacy of LASIK and secondary piggyback IOL implantation for the enhancement after cataract surgery. Russian Journal of Clinical Ophthalmology. 2020;20(3):122–127. DOI: 10.32364/2311-7729-2020-20-3-122-127.